The inhibitory receptor LAG3 affects NK cell IFN-γ production through glycolysis and the PSAT1/STAT1/IFNG pathway - Ge, Hongchi; Guo, Nan; Liu, Yufei; Lang, Bin; Yin, Xiaowan; Yu, Xiaowen; Zhang, Zining; Fu, Yajing; Ding, Haibo; Hu, Qinghai; Han, Xiaoxu; Geng, Wenqing; et al. (mBio, 2025)
We demonstrate that lymphocyte activation gene 3 (LAG3) expression is upregulated on natural killer (NK) cells during HIV infection. LAG3 inhibits glycolysis in NK cells and also upregulates PSAT1 expression to suppress activation of the STAT1/IFNG pathway, thus restricting interferon-gamma production by NK cells. These results provide new clues to study the effects of LAG3 on the metabolism and functional exhaustion of NK cells and offer a potential target for the treatment of HIV.